Induction of NETosis in ovine colostral PMN upon exposure to Neospora caninum tachyzoites - Demattio, Lukas; Conejeros, Ivan; Grob, Daniela; Gärtner, Ulrich; Taubert, Anja; Hermosilla, Carlos; Wehrend, Axel (Frontiers in Veterinary Science, 2023)
Colostrum is one of the most important factors influencing the health and development of mammalian neonates. It is well-established that leukocytes, including polymorphonuclear neutrophils (PMN), migrate from the mother to the infant via colostrum uptake. In this study, for the first time, we studied the ability of ovine colostral-derived PMN to extrude neutrophil extracellular traps (NETs) against the abortive apicomplexan parasite Neospora caninum. Although this cell population plays a significant role in the transmission of maternal innate immunity to neonates, little is known about colostral PMN activities in sheep. However, this cell population is a significant source of the transfer of maternal immunity to the neonate. Colostral PMN continues to exert immunological effects even after transitioning into the colostrum. The present study aimed to investigate the extrusion of NETs by ovine colostral PMN exposed to the apicomplexan parasite, N. caninum, which is known to cause devastating reproductive disorders in cattle, small ruminants, wildlife animals, and dogs. The present study is the first to demonstrate that ovine colostral PMN can produce NETs after stimulation with vital N. caninum tachyzoites. Ovine colostrum-derived NETs were detected by chromatin staining and antibody-based immunofluorescence staining of NET-specific structures, including neutrophil elastase (NE) and global histones (H1, H2A/H2B, H3, H4), as well as scanning electron microscopy (SEM) analysis.